(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The research paper aims at developing the awareness of digital literacy. Digital Literacy develops good skills to deal with the appropriate digital tools and knowing variety types of digital tools which can be use in digital literacy among people. The integration of many applications of ICTs, including different software systems and technology tools into the educational process and their successful use changes the content, methods and forms of training. The acquisition of skills and competencies in the digital age presupposes a new way of thinking and the ability of the user to continuously adapt to the new literacy required by the new technologies.